The work of the Prague creative period of archpriest Sergius Bulgakov «The old and the new» (to the discovery of the autograph manuscript) - Ionov Aleksandr, priest (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2013)
It is the first publication in Russian of the article «The Old and the New», written by Fr Sergius Bulgakov in 1923. The article provides (in the broader context of the long history and prospects of the development of Christian civilization) understanding of such phenomena and events in the life of the Russian Church, as the fall of the Orthodox monarchy, «church revolution» in the spring and summer of 1917, the Local Council of 1917–1918, beginning and forms of persecutions against the faith and the Church, the person and the feat of Patriarch Tikhon, Council of the Russian Orthodox Church Abroad in Sremski Karlovci, renovationist dissidence. In the introductory article the publisher characterize the place of this work in the context of the creativity of Fr Bulgakov, history and peculiarities of recently found autograph manuscript (including the correlation to the translated versions that were published earlier).